2018
DOI: 10.1016/j.jcmg.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Sex Dimorphism in the Myocardial Response to Aortic Stenosis

Abstract: ObjectivesThe goal of this study was to explore sex differences in myocardial remodeling in aortic stenosis (AS) by using echocardiography, cardiac magnetic resonance (CMR), and biomarkers.BackgroundAS is a disease of both valve and left ventricle (LV). Sex differences in LV remodeling are reported in AS and may play a role in disease phenotyping.MethodsThis study was a prospective assessment of patients awaiting surgical valve replacement for severe AS using echocardiography, the 6-min walking test, biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 43 publications
(56 reference statements)
5
57
2
Order By: Relevance
“…Myocyte death is central to the development of replacement fibrosis and it is possible that the different impact of these sex hormones on myocyte survival contributes to a higher prevalence of replacement fibrosis in men. A sex disparity in the prevalence of replacement fibrosis in DCM is consistent with other studies and has also been demonstrated in acute myocarditis and aortic stenosis . Other studies have demonstrated sex differences in gene expression in patients presenting with HF secondary to DCM and these may be responsible for differences in phenotype and outcome …”
Section: Discussionsupporting
confidence: 87%
“…Myocyte death is central to the development of replacement fibrosis and it is possible that the different impact of these sex hormones on myocyte survival contributes to a higher prevalence of replacement fibrosis in men. A sex disparity in the prevalence of replacement fibrosis in DCM is consistent with other studies and has also been demonstrated in acute myocarditis and aortic stenosis . Other studies have demonstrated sex differences in gene expression in patients presenting with HF secondary to DCM and these may be responsible for differences in phenotype and outcome …”
Section: Discussionsupporting
confidence: 87%
“…In our study, gender and diabetes were unevenly distributed between the groups, while for the BMI there was a trend in being higher in the group with "inappropriate" hypertrophy ( Table 1). The gender issue was in line with other studies in which was demonstrated that male gender easily develops a higher LVM, fibrosis deposition and LV dysfunction than females [34][35][36].…”
Section: Role Of Prosthesis Fluid Dynamicssupporting
confidence: 90%
“…Hypertension is one of the most frequent factor that may be responsible for the persistence of LV hypertrophy [6] along with the high stiffness of the vascular system, resulting in a high arterial impedance or Zva [37]. These two conditions hamper LV mass regression both pre-operatively, with the deposition of irreversible fibrosis [11,20,23], and post-operatively if the hypertension is not adequately treated or a high LV impedance persists [6,36]. Apparently, this was not the case in our study, because both hypertension incidence and the level of the Zva and arterial compliance were similar in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional wisdom holds that women more often present higher RWT and lower LV sizes when compared to men . However, more recent studies using cardiac magnetic resonance revealed that in AS women tolerate pressure overload with less concentric remodeling …”
Section: Discussionmentioning
confidence: 99%